Remission from depression is associated with improved quality of life and preserved exercise capacity in adults with congenital heart disease - Fillies, Brit; Stapel, Britta; Lemke, Lars H.; Löffler, Friederike; Bauersachs, Johann; Kahl, Kai G.; Westhoff-Bleck, Mechthild (Frontiers in Cardiovascular Medicine, 2024)
Aims Improved long-term survival has widened the treatment goals for adults with congenital heart disease (ACHD) by addressing parameters that impact mental well-being and exercise capacity. Depression, a frequent co-morbidity in ACHD, is linked to both. Whether successful treatment of depression also affects cardiac parameters is a matter of debate. Methods This prospective, cross-sectional, longitudinal study included N = 150 ACHD (mean age 35.2 ± 11.3 years, 57% male) at baseline (t0) and N = 114 at follow-up (mean follow-up: 4.8 ± 0.6 years; t1). Patients were interviewed using a structured clinical interview, and severity of depression was assessed using the Montgomery-Asperg Depression Scale (MADRS). Additional testing was performed using self-rating questionnaires concerning depression, anxiety and quality of life (QoL). Exercise capacity (VO2max) was assessed by symptom limited exercise testing. Results Of N = 33 patients diagnosed with depression at t0, N = 18 patients remitted and N = 15 were non-remitters. Remitters displayed significantly decreased anxiety (P = 0.013), improved global QoL (P = 0.002), and preserved VO2max (P = 0.958) at t1 compared to t0. This was associated with favourable health behaviour at t1 and stable body-mass-index. Contrarily, non-remitters reported further increased anxiety (P = 0.021) and no significant improvement in QoL (P = 0.405). VO2max declined significantly (P = 0.006) and body-mass-index increased (P = 0.004). Never-depressed patients showed no significant changes in anxiety (P = 0.415) or QoL (P = 0.211). VO2max decreased significantly (P < 0.001). Conclusion In ACHD, remission from depression is associated with better physical functioning, mental health, and QoL. The assessment and treatment of depression in ACHD emerges as an important clinical goal that should be included in a comprehensive multimodal treatment plan.